Perancangan Komunikasi Visual Film Animasi Pendek â€œDewi Yang Kesepianâ€ - Suryajaya, Pamela; Puspitasari, Dyah Gayatri (Bina Nusantara University, 2011)
This research is to gain, collecting, and analyze data needed to design short movie animation in 3 dimension technique about gods and goddesses myth in visually attractive so it could attract teenage audiences to send the message. The research method is direct survey to the location, i.e. Pura Merthasari, Wihara Dharma Bhakti (Klenteng Petak Sembilan), National Museum, and library. Besides, it is supported by literature media like books, magazines, and journals and internet references related to topic. The expected result is to reissue the cultural richness of myth in Indonesia so that it could be disseminated in to the myth animation film of gods and goddesses. The overall conclusion in today?s era is that visual communication media like film and television show are attracted teenagers. Therefore, by using animation film media, teenagers will be interested and attracted in national?s gods and goddesses myth, because the local show is just like international show.